MOTIVES OF STRUGGLES IN KHALED HOSSEINI’S NOVEL A THOUSAND SPLENDID SUNS - Any Suharni; Susi Ekalestari (JOURNAL OF LANGUAGE, 2019)
This study is an analysis of the aims of the protagonist’s struggle in Khaled Hosseini’s novel A Thousand Splendid Suns. The novel tells about a wife, the protagonist of the novel, who should live hard with a husband with bad temper. However, the protagonist by the name of Mariam keeps being a good wife for her husband. Furthermore, her husband has another wife. Unfortunately, the husband with his bad temper almost kills her. The protagonist should struggle to protect her husband’s another wife as well. The analysis is conducted by descriptive qualitative method, in which the data are analyzed descriptively. Some theories, concepts and notions of struggle are applied in this study to support the analysis and finding. One of the theories adopted in this study is proposed Flexner and Fitzpatrict (1996: 9) who said that the concepts of struggle is permeated from the history, the labor movement, and the place of working woman. It implies that the struggle of woman is rooted from the history, the labor movement, and the place of working woman.